Effect of anthelmintic treatment strategy on strongylid nematode species composition in grazing lambs in Scotland. Issue 1 (December 2016) - Melville, Lynsey A; McBean, David; Fyfe, Alex; Campbell, Sara-Jane; Palarea-Albaladejo, Javier; Kenyon, Fiona
Abstract Background Refugia based anthelmintic protocols aim to reduce the rate of development of anthelmintic resistance in gastrointestinal nematodes (GIN). Previous studies have illustrated the impact of different drenching regimes on drug efficacy and animal growth; however, the impact on nematode populations has yet to be characterised within natural infections. This study investigated the changes in species composition of GIN throughout the grazing season, following implementation of four different ivermectin drenching regimes over six years: neo-suppressive monthly treatment (NST), targeted selective treatment (TST), strategic prophylactic treatment (SPT) and treatment upon observation of clinical signs (MT). Methods Lambs were grazed on one of eight replicate paddocks each grazing season following treatment regimes assigned in year 1. Faecal samples were collected fortnightly from all animals and hatched to first stage larvae (L1 ). DNA was extracted from individual L1 and a multiplex PCR assay targeting the internal transcribed spacer 2 (ITS2) region ofTeladorsagia circumcincta, Trichostrongylus spp. andHaemonchus contortus conducted. Other species were identified using species-specific PCR. Worm-naïve tracer lambs were grazed on the paddocks at the start and end of each grazing season and adult worms recovered at post mortem to investigate the parasite population on pasture. Results Results showed an overall decrease in species diversity in egg output from the NST group which occurred within a single grazing season and was consistent throughout the experiment. Species diversity was protected over six years in groups implementing TST, SPT and MT treatment regimes, designed to offer refugia. The expected shift in species prevalence throughout the season fromTeladorsagia toTrichostrongylus was observed in all but the NST group where onlyTeladorsagia spp. were recovered from trial lambs by the end of the experiment. Worm burdens indicated the presence of several species at relatively low abundance on pasture in the NST group in 2011. However, these species were not represented in egg output from trial lambs, probably due to the frequent anthelmintic treatment administered throughout the grazing season. Conclusion The molecular methods utilised here worked well. The comparable results of the three refugia-based treatment regimes suggest that nematode diversity can be maintained using part or whole group treatments if a rich supra-population of parasites are available to re-infect animals post treatment.